Effects and influence of the urea component of an organomineral fertiliser on phosphorus mineralisation in a low-P index arable and grassland soil - Abubakar, Musa Ahmad (Cranfield University, 2016)
Addition of organic waste such as sewage sludge (biosolids) has been recognised as one of the cost effective method of waste recycling practice of maintaining levels of organic matter in agriculture. Biosolids are a slow-release nutrient (N and P) which also improves soil physical and microbiological properties and as such offer a promising plant nutrient with less impact on soil than mineral fertilisers. Implementation of wastewater treatment directive 91/271//EC has caused large amount of sewage sludge production and availability. Hence, management of biosolids to provide available phosphorus through soil recycling would reduce reliance on finite rock phosphates (over 85% P-fertilisers) extraction, protect or minimise environmental problems such as eutrophication and also help the resource-limited farmers particularly in developing countries, to mitigate P-fertiliser limitation in the soil. More awareness of the impact of different agricultural fertiliser management practices on soil quality and sustainability has led to more interest of combining organic residuals with inorganic fertilisers to prevent further fertility decline and degradation of soil. Amongst recent nutrient integration, was the nutrient-balanced sludge-based (biosolids with urea and potash) called organomineral fertiliser (OMF), which shows agronomic efficiency of phosphorus management when applied to the field crops such as winter wheat. However, to manage phosphorus mineralisation effectively in the organomineral fertiliser treated soil, it is important to understand the effects of urea components in OMF during mineralisation of phosphorus in soil. This research aimed to understand the influence that the urea component of an organomineral fertiliser (OMF) has during phosphorus mineralisation in soil. Therefore urea granules were grounded into powdered form and mixed with grounded biosolids pellets as a source of phosphorus to obtain organomineral fertilisers. This whole research included two different control soil incubation experiments (1a & 1b) both observed over a 60 days period. Incubation experiment 1a (involved mixing various rates of biosolids and urea in soil) had two different soil samples from the grassland (sandy clay loam) and arable (clay loam) sites. In terms of initial soil phosphorus content, the grassland and arable soils are classified as P-index 1 and 2 respectively. Soil samples were analysed for pH, mineralisable nitrogen (NH4 + , NO3 - ), available phosphorus, microbial biomass carbon and phosphorus and phospholipids fatty acids profiles during 0, 6, 15, 20, 35, 45 and 60 days incubation period. While in the incubation experiment 1b (mixing different rates of urea with fixed quantity of biosolids in soil), soil from the same grassland, were being sampled at 10 day intervals (10, 20, 30, 40, 50, and 60) after taking the initial sample of day 0 and analysed for pH, mineralisable P and phosphomonoesterase enzyme activities. The incubation experiments showed that, mineralisation of available phosphorus were significantly (p<0.001) higher in the biosolids and organomineral (OMF) fertiliser treated soils compared to control during 20 and 30 days period. The mean values of mineralisable P from OMF treatment for the incubation experiment 1a were 14.5 and 19.5 mg/kg in the grass and arable soils respectively. The mineralisation rates of biosolids-P from organomineral fertiliser (OMF) amended soils were also reduced significantly, as the dosages of urea component were increased according to the 50, 150 and 250Kg/N equivalents during the 60 days incubation experiment 1b. The mean available P values from the OMF amendments were 28.0, 25.7 and 23.4mg/kg respectively; according to the increasing amount of urea content at 50, 150 and 250Kg/N equivalents respectively. The overall trend of organomineral fertiliser phosphorus (OMF-P) mineralisation rate have shown significant (p<0.001) reduction with increased doses of urea components, with the fixed biosolids equivalent rate of 250Kg/ha during the incubation experiment 1b. There were no significant (p>0.01) changes in pH from both soil incubation experiment 1a and 1b, except for the urea only treated samples at the 250KgN/ha equivalent rate from the sandy clay loam grassland soil, which shows up to 1 unit increase (pH=8.1) compared to other treatments, just a day after kick-starting the incubation experiment, but eventually becomes reduced to the original pH (6.9) during the incubation period. Microbial community change in both arable and grassland soil from initial day zero showed distinct and consistent shifts in trends through the 20 and 45 days respectively, irrespective of their treatments, and then gradually shifted towards the original starting point at the final incubation study of day 60. This was however attributed to the function of change with time, since it could not be categorically assigned to the OMF application effects only, but perhaps community change effects with time could be the main factor. Even though there was no any important patterns or trends observed between the indigenous treatments, but the wide spreading and shift distances amongst treatments during 20 and 45 days were higher compared to the 0 and 60 days, and this is probably because there were more phosphorus mineralisation when microorganisms were able to access more dissolved organic carbon as shown by high biomass carbon during 20 and 35 days incubation time, and utilise it to generate energy that kept them more active within those period before it gradually becomes exhausted, since there was no external source of energy being added. Similarly, phosphomonoesterase enzyme activities in the soil treatments except for the urea only amended samples, showed significant (p<0.01) differences between days 20, 30 and 40 compared to days 0, 50 and 60 and the phosphatase activities in the OMF amendments had significantly higher acid than alkaline phosphatase activities. Organomineral phosphorus (OMF-P) mineralisation in soil during 60 days incubation in this short-term study have shown potential P release in both soils, and the OMF-P mineralisation rate was highest in the formulation having fixed biosolids with urea at 150KgN/ha equivalent compared to other formulations (50KgN/ha and 250KgN/ha) and therefore effects of urea component of the organomineral fertiliser is an important factor when considering OMF as a promising P alternative or source in low-P soil during phosphorus management. Appropriate product formulation depending on the crop needs is therefore very important for soil phosphorus nutrient management and sustainability.
Keywords: Organomineral fertiliser; Phospholipids fatty acid analysis; microbial biomass carbon and phosphorus; available phosphorus; total oxide of nitrogen phosphomonoesterases; enzyme activity